Due Cartografie Regionali a Confronto (GEOmedia, 2025)
It all started, here, in the late 1960s. Until then, the only general cartography in existence was the IGM at 1.25000 scale, and the cadastral one at 2000; different in representation, in reference, in purposes and in short in everything.At the initiative of the Italian Society of Topography and Photogrammetry, a conference was held in Milan, under the aegis of the Regional Commission for Economic Programming, directed by the then president Piero Bassetti, during which the foundations of the future Regional Technical Maps, the current “CTR”, were laid.